Para‐Hisian pacing: The eyes see what the mind knows. Issue 5 (5th August 2022) - Jain, Ashish; Bootla, Dinakar; Balaguru, Sridhar; Selvaraj, Raja J.
Abstract : A young male presented with pre‐excited atrial fibrillation. During an electrophysiology study, preexcitation suggestive of a pathway in posteroseptal location was confirmed but no tachycardia was inducible. Para‐Hisian pacing was done during sinus rhythm. Is there retrograde conduction through the accessory pathway?